Space, Identity, and Religion: Balinese Migration in South Lampung (1905–2012) - M. Nehza Rausan Shadra, M. Nehza Rausan Shadra; Ronal Ridhoi, Ronal Ridhoi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2025)
This study examines Balinese migration to South Lampung from the colonial period through the New Order era, as well as its impact on the formation of cultural identity and socio-religious relations with the local Muslim community. The main issue raised is how state-driven migration policies engineered demographic transformations, created cultural enclaves, and influenced the dynamics of life in multicultural areas. Using a qualitative-historical approach based on a literature review, this research analyzes three theoretical frameworks: Henri Lefebvre's production of social space, Stuart Hall's concept of diaspora identity, and Max Weber's sociology of religion. The results show that Balinese migration is a state-engineered social space project (conceived space), which has led to the creation of Hindu-Balinese enclaves alongside Muslim villages in Lampung, thus establishing symbolic boundaries within a shared social space. In this context, the Balinese community maintains its dual identity, preserving its cultural and religious traditions (being), while also adapting to Lampung Islamic culture (becoming). Meanwhile, Weber's concept of religious ethics reveals a dual role: promoting economic cooperation and integration, yet also serving as a source of segregation and conflict when structural problems like economic and land inequality arise. The 2012 Balinuraga incident was the culmination of this accumulated tension. This study concludes that the interaction of space, identity, and religious ethics explains the patterns of integration and conflict in South Lampung. Theoretically, these findings extend the application of Lefebvre, Hall, and Weber's theories within the Indonesian context, while also emphasizing the practical importance of resource equity and interfaith dialogue in maintaining harmony in a multicultural society.